Retained placenta in Relation with Blood Components in Egyptian crossbred cattle - Reem S. Mourad (Jurnal Ilmu Ternak dan Veteriner, 2019)
The present study was carried out in the veterinary units on 14 normal cows and 32 cows with Retained Placenta. Cows were chosen after about 6 to 12 hours from parturition in Shebin Elkom, Menoufia, Egypt.        Results show that there was very highly significant increase of concentrations of all blood biochemical components, macro elements and micro elements in normal cows than those in retained fetal membranes cows except in globulin, Sodium and Manganese.  On the other hand, plasma concentrations of biochemical components were highly significant between summer and winter in cholesterol, total protein and albumin but it wasn’t significant in glucose, globulin and A/G ratio. Moreover, there was very highly significant in plasma concentration between summer and winter in all macro elements except potassium and Ca/P ratio. Also, there was very highly significant in plasma concentration between summer and winter in all micro elements except Manganese. Meanwhile, plasma concentrations of biochemical components were not significant between parities except in A/G ratio. Furthermore, there was no significant in plasma concentration between summer and winter in all macro elements. But, there was very highly significant (P≤0.01) in plasma concentration of Cu and Cd between summer and winter, and it was significant (P≤0.05) in Fe and Se but, there was no significant in Co, Zn, Mn, and Mo.      The aim of this study was to determine blood plasma constituents and inorganic macro and micro elements in the case of retained placenta in crossbred cattle under Egyptian conditions.